2018
DOI: 10.1002/zoo.21433
|View full text |Cite
|
Sign up to set email alerts
|

The effects of zoo visitors on Quokka (Setonix brachyurus) avoidance behavior in a walk‐through exhibit

Abstract: The behavior of zoo animals may be influenced by visitors, with possible implications on animal welfare. We examined the effects of the presence of visitors on the presence and visibility of free‐ranging quokkas (Setonix brachyurus) in preferred areas of a walk‐through enclosure at Melbourne Zoo, Australia. In a controlled experiment, two visitor treatments were randomly imposed: (1) enclosure open to visitors as normal (“Open”) and (2) enclosure closed to visitors (“Closed”). Treatments were imposed for 2‐day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 38 publications
(54 reference statements)
1
27
0
Order By: Relevance
“…It was found that the orangutans showed a preference to position themselves in front of the open window. Other studies have experimentally blocked access to visitors on some days to investigate the effect of presence or absence of visitors on animals [53,76]. When visitors were blocked from an exhibit, little penguins showed less aggression, huddling and avoidance behavior [53], and when visitors were blocked from a quokka exhibit, more quokkas were visible from the visitor pathways [76].…”
Section: Assessment Of the Visitor Effectmentioning
confidence: 99%
“…It was found that the orangutans showed a preference to position themselves in front of the open window. Other studies have experimentally blocked access to visitors on some days to investigate the effect of presence or absence of visitors on animals [53,76]. When visitors were blocked from an exhibit, little penguins showed less aggression, huddling and avoidance behavior [53], and when visitors were blocked from a quokka exhibit, more quokkas were visible from the visitor pathways [76].…”
Section: Assessment Of the Visitor Effectmentioning
confidence: 99%
“…However, results from these four studies need to be interpreted with caution as three of the above-mentioned studies examined correlations between visitor numbers and penguin behaviour [13,15,16], and only one study was under experimental conditions [14]. Also, this variation in penguin behaviour related to visitor contact may be due to species or individual animal differences, such as past experiences and coping style, enclosure design or the nature of the visitor interactions [17]. Consequently, it remains unclear what aspect of visitor contact affects penguin behavioural responses.…”
Section: Introductionmentioning
confidence: 99%
“…When multiple exhibit types were studied, Bennett’s wallabies ( Macropus rufogriseus ) fed more and exhibited more interactive behaviors in the no-interaction exhibits; however, resting, locomotion, and vigilance did not differ between exhibit types [ 49 ]. In addition, quokka ( Setonix brachyurus ) were less likely to be visible when visitors were present in walk-though exhibits, but the effect of visitor presence was not considered to be great [ 50 ].…”
Section: Introductionmentioning
confidence: 99%